Economic Growth, CO2 Emissions, Electricity Production, and Consumption Nexus in Bangladesh - Islam, Nazrul (Asian Business Review, 2021)
This paper seeks to find the causal relationship between economic growth, electricity consumption, carbon emissions, electricity production from oil, and electricity production from gas. The data were taken from World Development Index (WDI) for the period of 1972-2014. For stationarity checking, visualization and some econometrics techniques like ADF and Phillips-Perron test have been adopted. For testing the long-run relationships among the variables, the Johansen cointegration testing procedure has been considered. This test ensured that there are long-run relationships among the variables. To capture the short-run dynamics, a VECM test has been done, and to find the direction of causation, the Granger causality approach has been tested. The results find that there was a bidirectional causality from CO2 emissions to gross domestic product (GDP) and from electricity production from gas to GDP where unidirectional causality was found from GDP to electricity consumption and electricity production from oil to GDP. CUMSUM and CUSUM approaches have also been considered to test the stability of the parameters. Policy implications of the research indicate that Bangladesh should give importance to low carbon emission technologies to reduce the CO2 emissions level with a view to keeping Bangladesh safe from natural calamities along with economic growth.JEL Classifications: C32, O13, Q43
Keywords: Electricity Production; Electricity Consumption; CO2; GDP; Causality